Defining the low‐risk salvage laryngectomy—A single‐center retrospective analysis of pharyngocutaneous fistula. Issue 2 (23rd March 2018) - Vasani, Sarju S.; Youssef, Daniel; Lin, Charles; Wellham, Annabelle; Hodge, Robert
Abstract : Objectives: Salvage total laryngectomies (STL) are not a homogeneous group. Most will fall into two groups: i) Patients with previous AJCC stage I/II larynx cancer who have had radiotherapy to the larynx only (STL‐LOR), or ii) Patients who have had previous AJCC stage III/IV larynx cancer and subsequent radiotherapy to the larynx and draining nodal basins with concurrent cisplatin chemotherapy (STL‐CRT). We aimed to compare PCF rates following STL in these two groups. Methods: A retrospective review of the department's cohort between January 2010 and August 2015 was conducted. Results: Seventy‐seven patients underwent total laryngectomy for larynx cancer between January 2010 and August 2015. There were 10 post‐laryngectomy fistulas (13.0%). Three of these occurred in the 38 patients undergoing primary total laryngectomy (PTL), and seven in the 39 patients undergoing STL, rates of 7.9% and 17.9%, respectively. Twenty‐two patients had received radiation to the larynx alone without chemotherapy (STL‐LOR) for initial Stage I/II disease. Eleven patients had received laryngeal and neck irradiation plus cisplatin chemotherapy (STL‐CRT) for initial stage III/IV disease. Of the 22 STL‐LOR patients, two developed PCF (9.1%). Of the 11 STL‐CRT patients, five developed PCF. There was no difference in the rate of PCF between PTL and STL‐LOR. There was a statistically significant increase in PCF in STL‐CRT versus PTL ( p = .009) and in PCF in STL‐CRT versus STL‐LOR ( p = .027). Conclusion: Salvage laryngectomies are often treated as a homogenous group. We demonstrate that PCF rates vary significantly depending on preoperative radiation fields and the use of chemotherapy. Level of Evidence: 2b.